Experimental analysis of diffusion absorption refrigerator driven by electrical heater and engine exhaust gas - ADJIBADE, Mohamed Izzedine Serge; THIAM, Ababacar; AWANTO, Christophe (My University, 2017)
This work presents an experimental study of H20-NH3-H2 diffusion absorption refrigeration under two types of energy sources, i.e. the conventional electric energy from grid (electric) and exhaust gas from internal combustion engine. Dynamic method is used to evaluate the behavior of the components of the system for both energy sources. Results obtained show that the performance of each component under different types of energy sources is almost coherent. For the generator, the electrical heater system requires more time to warm up, around three minutes, compared to the 40 s for system running with exhaust gas. For the evaporator, the decreasing rate is higher for the exhaust gas source and it took only about two hours to reach steady-state while for the electrical heat, the steady-state is reached after about seven hours of operation. For both energy sources, the evaporation temperature stabilizes to 3 °C and the minimum temperature to boil off ammonia is around 140 °C.
Keywords: Diffusion absorption chiller; Experimental; Transient state; Exhaust gas; Electrical heater; Water-ammonia-hydrogen